Tackling the emergency powers that shaped the legal landscape during COVID-19: Analysing the legal disruptions and regulatory solutions - Vasilka Salevska-Trajkova (University American College Skopje, 2021)
When speaking of extraordinary powers, we usually think of powers available to the executive during times of emergency. The outbreak of COVID-19 has impacted fundamentally the functioning of States, their democratic institutions and legal systems. Therefore, it is understandable that governments are continuing to resort to exceptional measures in seeking to get control over the spread of COVID-19. These exceptional measures inevitably restrict rights and institutional actions in ways that can be justified only in these extraordinary circumstances. It is in the greatest interest of society that these measures against COVID-19 are imposed and enforced within the framework of established democratic principles, the international legal order and the rule of law. While some constitutions include detailed rules providing for a state of emergency (sometimes of various kinds) in the event of external or internal threats, others address emergencies by making use of rules that allow for a certain modification of the normal balance of powers between the executive and legislative powers. Interestingly, however, even where specific emergency constitutional mechanisms exist, Member States have preferred not to trigger them, either for historical reasons or for fear of triggering a mechanism perceived as too repressive. Legislation adopted in situations of emergency raises questions as to temporal limitations, scope and proportionality and legal certainty. This paper will analyze the extraordinary public powers that are usually reserved for emergency situations in which ordinary public powers are not sufficient to effectively deal with a crisis. Ordinary constitutional processes are too slow to respond to the immediate needs of the population, so that they must be restricted to enable swift help and relief to those affected. The comparative analysis in several states will overview the effects of the extraordinary powers in the form of emergency powers provided for by emergency legislation.
Keywords: 330; COVID-19; extraordinary powers; state of emergency; constitution; regulatory management tools